Molecular Phylogeny and Biogeography of Adenocaulon Highlight the Biogeographic Links between New World and Old World - Deng, Tao; Chen, Yongsheng; Wang, Hengchang; Zhang, Xiaoshuang; Volis, Sergei; Yusupov, Ziyoviddin; Qian, Hong; Sun, Hang (Frontiers in Ecology and Evolution, 2018)
Adenocaulon (Asteraceae) is a small genus with only five species but has a broad amphi-Pacific distribution pattern with three species distributed disjunctly in South America, Central America and North America and two endemic species spanning eastern Asia to the Himalayas. To trace the biogeographic pattern of the genus, we reconstructed its phylogenetic relationships and diversification history based on one nuclear and eight plastid gene regions. Our results showed that Adenocaulon is monophyletic and may have originated in Central America during the Miocene, dispersed into North America and finally reached the Himalayas via the Bering Land Bridge. The hypothesized trajectory implies that long-distance dispersal may have played an important role in the formation of the distribution of this group of species. This hypothesis seems to have gained support from the special morphological structure of fruits of the genus.